Research on the Relationship between Carbon Precipitation and Mechanical Properties of Dissimilar Steel Welds. Issue 6 (January 2021) - Li, Xiuneng; Wu, Yuan Jian; Ding, Min; Yan, He; Yang, Chao; Du, Liang; Guo, Hong
Abstract: After the room temperature tensile test of the pearlite heat-resistant steel and austenitic stainless steel welds after operation, it was found that 75% of the fracture locations were on the austenite side weld line and 25% of the fracture locations were on the austenite side. The maximum tensile strength of the pipe wall under the operating temperature of 530°C and 540°C is 480 MPa and 580 MPa, respectively. Metallographic examination found that there was a "uphill diffusion" near the weld. Through theoretical calculations, after 90, 000 hours of operation, on the austenite side of the weld, the difference in carbon increase in the "uphill diffusion" per unit area under the two conditions is about 1.3833E + 8. Based on the analysis of the relationship between the difference in carbon increment and the mechanical properties, it can be deduced that the dissimilar steel weld of this type of screen superheater tube can continue to serve for about 25, 000 hours.